Increased 1‐aminocyclopropane‐1‐carboxylate deaminase activity enhances Agrobacterium tumefaciens‐mediated gene delivery into plant cells. Issue 5 (2nd September 2013) - Someya, Tatsuhiko; Nonaka, Satoko; Nakamura, Kouji; Ezura, Hiroshi
Abstract Agrobacterium‐mediated transformation is a useful tool for the genetic modification in plants, although its efficiency is low for several plant species. Agrobacterium‐mediated transformation has three major steps in laboratory‐controlled experiments: the delivery of T‐DNA into plant cells, the selection of transformed plant cells, and the regeneration of whole plants from the selected cells. Each of these steps must be optimized to improve the efficiency of Agrobacterium‐mediated plant transformation. It has been reported that increasing the number of cells transformed by T‐DNA delivery can improve the frequency of stable transformation. Previously, we demonstrated that a reduction in ethylene production by plant cells during cocultivation with A. tumefaciens‐expressing 1‐aminocyclopropane‐1‐carboxylic acid (ACC) deaminase resulted in increased T‐DNA delivery into the plant cells. In this study, to further improve T‐DNA delivery by A. tumefaciens, we modified the expression cassette of the ACC deaminase gene using vir gene promoter sequences. The ACC deaminase gene driven by the virD1 promoter was expressed at a higher level, resulting in a higher ACC deaminase activity in this A. tumefaciens strain than in the strain with the lac promoter used in a previous study. The newly developed A. tumefaciens strain improves the delivery of T‐DNA into Solanum lycopersicum (tomato) and Erianthus ravennae plants and thus may be a powerful tool for the Agrobacterium‐mediated genetic engineering of plants.